Morbid Obesity as Early Manifestation of Occult Hypothalamic-Pituitary LCH with Delay in Treatment - Jennifer Keates-Baleeiro; Marielisa Rincon (Case Reports in Oncological Medicine)
Morbid obesity presents unique challenges in managing additional disease processes. A 16-year-old male with a history of central diabetes insipidus (DI) and hypothyroidism developed destructive lesions in both his right mandible and brain, which were not discovered until the patient presented for tinnitus, 8 years after his initial diagnosis with DI. Langerhans cell histiocytosis (LCH) was diagnosed on pathologic biopsy. The patient’s initial body mass index (BMI) was 54.5 kg/m2 so a unique treatment approach with single agent cladribine (2-CdA) was offered as traditional steroid therapy could worsen his endocrine dysfunction. The patient presented with neurodegenerative sequelae from the central LCH, possibly due to a delay in diagnosis and therapy. This case highlights difficulties in managing obese patients in an oncology setting and provides an illustrative case of how obesity may mask other comorbid conditions. Close supervision of complex obese patients with coordinated endocrinology and oncology care is vital. For the primary care practitioner, monitoring abrupt changes in BMI with serial cranial imaging may lead to a prompt diagnosis and prevention of further neurodegenerative effects. The use of 2-CdA was found to successfully bring the patient’s LCH into remission without the additional risks of steroid therapy in a morbidly obese patient.